Double-Sided Energy Auction in Microgrid: Equilibrium under Price Anticipation - Faqiry, M. Nazif; Das, Sanjoy (My University, 2017)
This paper investigates the problem of proportionally fair double-sided energy auction involving buying and selling agents. The grid is assumed to be operating under islanded mode. A distributed auction algorithm that can be implemented by an aggregator, as well as a possible approach by which the agents may approximate price anticipation is considered. Equilibrium conditions arising due to price anticipation is analyzed. A modified auction to mitigate the resulting loss in efficiency due to such behavior is suggested. This modified auction allows the aggregate social welfare of the agents to be arbitrarily close to that attainable with price taking agents. Next, equilibrium conditions when the aggregator collects a surcharge price per unit of energy traded is examined. A bi-objective optimization problem is identified that takes into account both the agents' social welfare as well as the aggregator's revenue from the surcharge. The results of extensive simulations, which corroborate the theoretical analysis, are reported. © 2013 IEEE.
Citation: Faqiry, M. N., & Das, S. (2016). Double-Sided Energy Auction in Microgrid: Equilibrium under Price Anticipation. Ieee Access, 4, 3794-3805. doi:10.1109/ACCESS.2016.2591912
Keywords: Agents; Aggregator; Auction; Bid; Energy Grid; Microgrid